Application of a rolled cookie laboratory exercise as a method for students to gain undergraduate research experience in food science. Issue 3 (13th May 2020) - Heermann, Melanie L.; Getty, Kelly J. K.; Yucel, Umut
Abstract: Hands‐on learning is a proven method of improving students' critical thinking skills. Undergraduate research projects are encouraged to help students develop research and laboratory skills. If properly designed and implemented, research opportunities can be embedded in existing student coursework, which increases the number of students who can participate in these research opportunities. Objectives of this study were twofold: (a) to determine students' perceptions of an undergraduate research laboratory exercise and (b) provide an innovative laboratory exercise for instructors to implement in their own classrooms. Rolled cookies were prepared by a food science class according to American Association of Cereal Chemists Method 10–50.05, using sucrose and alternative sweeteners and evaluated for physicochemical and organoleptic attributes. After completing the exercise, students evaluated cookie physical/organoleptic properties using a hedonic scale, were asked about personal demographics, and were surveyed about research/writing skills and food processing knowledge using a Likert scale. Approximately 50% of the class responded to the 2018 survey and nearly 85% responded to the 2019 survey. On average, 81.6% of students responded with "Strongly Agree" or "Somewhat Agree" to all survey questions, including data collection and analysis, critical thinking skills, experimental design, and replications. Students responded that detailed instructions provided by instructors were beneficial to their ability to understand experimental design, scientific communication, and the importance of using scientific resources.